2022
DOI: 10.3390/foods11060846
|View full text |Cite
|
Sign up to set email alerts
|

Proposing Two Local Modeling Approaches for Discriminating PGI Sunite Lamb from Other Origins Using Stable Isotopes and Machine Learning

Abstract: For the protection of Protected Geographical Indication (PGI) Sunite lamb, PGI Sunite lamb samples and lamb samples from two other banners in the Inner Mongolia autonomous region were distinguished by stable isotopes (δ13C, δ15N, δ2H, and δ18O) and two local modeling approaches. In terms of the main characteristics and predictive performance, local modeling was better than global modeling. The accuracies of five local models (LDA, RF, SVM, BPNN, and KNN) obtained by the Adaptive Kennard–Stone algorithm were 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Zhao et al [2] discriminated the lamb meat quality of Protected Geographical Indication (PGI) Sunite lamb, from two other banners in the Inner Mongolia autonomous region by stable isotopes and modeling. They found that this methodology, in conjunction with chemometric approaches such as the data-driven soft independent modeling of class analogy (DD-SIMCA), can be used as an effective indicator for protecting PGI Sunite lamb, taking into account geographical origin, feeding system, age, and gender.…”
mentioning
confidence: 99%
“…Zhao et al [2] discriminated the lamb meat quality of Protected Geographical Indication (PGI) Sunite lamb, from two other banners in the Inner Mongolia autonomous region by stable isotopes and modeling. They found that this methodology, in conjunction with chemometric approaches such as the data-driven soft independent modeling of class analogy (DD-SIMCA), can be used as an effective indicator for protecting PGI Sunite lamb, taking into account geographical origin, feeding system, age, and gender.…”
mentioning
confidence: 99%